The spatial analysis of digital economy and urban development: A case study in Hangzhou, China - Zhu, Wenjing; Chen, Jianjun (Cities, 2022)
The digital economy spatial distribution (DESD) analysis and urban development differ from the traditional pattern of a core-edge spatial model, highlighting the importance of a policy paradigm in a digital era. There are few empirical studies on the digital economy and urban development, especially urban development driven by the digital economy and the overall urbanisation. This paper attempts to reveal the policy guidance of DESD and its relationship with urban development. The primary objective is to figure out the DESD and urban development pattern, which could provide references for cities that want to realise city transformations through an upgrading process of both the economy and the city. Using an integrated approach that combines the policy analysis and several geographic outcomes, Hangzhou's DESD and urban development were studied based on three timestamps of 2001, 2010, and 2017. Subsequently, the spatial econometric and VAR methods were applied further to comprehend the digital economy and overall urbanisation. The discoveries reveal that the policy-oriented development strategy is conducive to breaking the constraints of the core-edge structure. However, the urban development driven by the digital economy and the urbanisation in general of Hangzhou is not entirely consistent. Under the dual role of economic policy and urban strategy, the digital economy plays a much more critical role in shaping urban spatial than urbanisation in general. •The economics and geographic methods are used to implement the study above 224 listed digital economy companies.•The pace of urban development and digital economy spatial distribution of Hangzhou are consistent.•The overall situation of Hangzhou digital economy is in a total agglomeration state.•The policy-oriented development model is an indispensable driven factor.